Practically religious : worldly benefits and the common religion of Japan - Reader, Ian, 1949- (University of Hawaiì Press, 1998)
Praying for practical benefits (genze riyaku) is a common religious activity in Japan. Despite its widespread nature and the vast numbers of people who pray and purchase amulets and talismans for everything from traffic safety and education success to business prosperity and protection from disease, the practice has been virtually ignored in academic studies or relegated to the margins as a uh_product of superstition or an aberration from the true dynamics of religion. Basing their work on a fusion of textual, ethnographic, historical, and contemporary studies, the authors of this volume demonstrate the fallacy of such views, showing that, far from being marginal, the concepts and practices surrounding genze riyaku lie at the very heart of the Japanese religious world. They thrive not only as popular religious expression but are supported by the doctrinal structures of most Buddhist sects, are ordained in religious scriptures, and are promoted by monastic training centers, shrines, and temples. Benefits are both sought and bought, and the authors discuss the economic and commercial aspects of how and why institutions promote practical benefits. They draw attention to the dynamism and flexibility in the religious marketplace, where new products are offered in response to changing needs. Intertwined in these economic activities and motivations are the truth claims that underpin and justify the promotion and practice of benefits. The authors also examine the business of guidebooks, which combine travel information with religious advice, including humorous and distinctive forms of prayer for the protection against embarrassing physical problems and sexual diseases. Written in a direct and engaging style, Practically Religious will appeal to a wide range of readers and will be especially valuable to those interested in religion, anthropology, Buddhist studies, sociology, and Japanese studies.